Spatial Analysis Of Environmental Factors On Malaria Incidence In The Working Area Of Bener Health Center, Purworejo Regency - Dian Eka Pratiwi; Mursid Raharjo; Onny Setiani (Jurnal Impresi Indonesia, 2025)
The Bener Health Center is one of the highest contributors to malaria cases in Purworejo District. In 2023, there were 134 malaria cases with an API of 2.25 per 1,000 population spread across 14 villages at the Bener Health Center. This study aims to determine the relationship between environmental factors and malaria incidence in the working area of Bener Health Center through a spatial approach. This study is a descriptive-analytical observational study with a case-control design. The case population in this study consists of 134 individuals, while the control population comprises 59,457 individuals. The sample size for this study is 81 cases and 81 controls. Data were collected through interviews and observations. Data analysis included statistical analysis (univariate, bivariate, multivariate) and spatial analysis. Bivariate analysis showed a relationship between the absence of wire netting (p-value = 0.024 and OR = 2.567), the presence of livestock shelters (p-value = 0.039 and OR = 2.029), and the presence of breeding places (p-value = 0.008 and OR = 3.403) with malaria incidence. Multivariate analysis showed that the absence of wire netting, the presence of livestock shelters, and the presence of breeding places simultaneously influenced the incidence of malaria in the working area of Bener Health Center. The distribution of malaria cases in the working area of Bener Health Center showed a clustered pattern.